Relationship of Clinical Manifestations of Heart Connective Tissue Dysplasis with Indicators of Hydroxyprolin Level and Mineral Imbalance (Global Journal of Medical Research, 2020)
Connective tissue dysplasia is a unique ontogenetic anomaly in the development of the body, which is one of the complex, far from studied questions of modern medicine, and is the morphological basis of functional changes in cardiac activity. We studied 115 children of preschool and school age with connective tissue dysplasia and small heart development abnormalities. A high frequency of occurrence of external phenotypic markers was revealed for the syndrome of dysplasia of the connective tissue of the heart and stigma of embryogenesis. An increase in the average level of hydroxyproline in blood serum in children with small abnormalities of the development of the heart in combination with cardiovascular pathology and patterns characterizing the relationship of the clinical manifestations of the disease and mineral imbalance has been established.
Keywords: connective tissue dysplasia; small abnormalities of the development of the heart; hydroxyproline; trace elements; children